Contrasting effects on deep convective clouds by different types of aerosols - Jonathan H. Jiang (Nature Portfolio, 2018)
Aerosol effects on convection have been debated for decades when all types of aerosols are lumped together in the analyses. Using NASA satellite measurements, the authors find strong evidence that smoke inhibits convection but polluted continental aerosols invigorate convection.